Risk of sudden unexpected death in epilepsy (SUDEP) with lamotrigine and other sodium channel‐modulating antiseizure medications - Russell Nightscales; Sarah Barnard; Juliana Laze; Zhibin Chen; Gerard Tao; Clarissa Auvrez; Shobi Sivathamboo; Mark J. Cook; Patrick Kwan; Daniel Friedman; Samuel F. Berkovic; Wendyl D'Souza; et al. (Epilepsia Open, 2023)
Abstract Objective In vitro data prompted U.S Food and Drug Administration warnings that lamotrigine, a common sodium channel modulating anti‐seizure medication (NaM‐ASM), could increase the risk of sudden death in patients with structural or ischaemic cardiac disease, however, its implications for Sudden Unexpected Death in Epilepsy (SUDEP) are unclear. Methods This retrospective, nested case–control study identified 101 sudden unexpected death in epilepsy (SUDEP) cases and 199 living epilepsy controls from Epilepsy Monitoring Units (EMUs) in Australia and the USA. Differences in proportions of lamotrigine and NaM‐ASM use were compared between cases and controls at the time of admission, and survival analyses from the time of admission up to 16 years were conducted. Multivariable logistic regression and survival analyses compared each ASM subgroup adjusting for SUDEP risk factors. Results Proportions of cases and controls prescribed lamotrigine (P = 0.166), one NaM‐ASM (P = 0.80), or ≥2NaM‐ASMs (P = 0.447) at EMU admission were not significantly different. Patients taking lamotrigine (adjusted hazard ratio [aHR] = 0.56; P = 0.054), one NaM‐ASM (aHR = 0.8; P = 0.588) or ≥2 NaM‐ASMs (aHR = 0.49; P = 0.139) at EMU admission were not at increased SUDEP risk up to 16 years following admission. Active tonic–clonic seizures at EMU admission associated with >2‐fold SUDEP risk, irrespective of lamotrigine (aHR = 2.24; P = 0.031) or NaM‐ASM use (aHR = 2.25; P = 0.029). Sensitivity analyses accounting for incomplete ASM data at follow‐up suggest undetected changes to ASM use are unlikely to alter our results. Significance This study provides additional evidence that lamotrigine and other NaM‐ASMs are unlikely to be associated with an increased long‐term risk of SUDEP, up to 16 years post‐EMU admission.